Assessment of oral hygiene practices among medical students - Gupta, Vineeta (International Journal Of Community Medicine And Public Health, 2020)
Background: Oral health is an important aspect of general health and wellbeing. As per available researches the high prevalence of oral diseases is a major public health problem. Oral hygiene is further compromised by unhealthy habits like tobacco use and lack of dental specialist care. Undergraduate medical and nursing students should be aware of oral health and dental hygiene as they are the future healthcare provider on whom the health of nation will depend. Methods: The present cross-sectional study was conducted at Raipur Institute of Medical Sciences, Raipur, Chhattisgarh, India during study period July 2019 to September 2019. Purposive sampling method was used to select M.B.B.S. and B.Sc. nursing students as study subjects. Only those students present in the college on the days of the data collection and those willing to participate were included in the study. Data (background information, awareness and practice regarding oral hygiene) was collected using a predesigned pretested questionnaire. Results: 52.7% of the study subjects were female and 47.3% were male. 7.9% students were confident of their healthy teeth and expressed as good and very good condition. All the students were brushing teeth daily and few students even brushed twice a day (30.7%). Frequency of changing toothbrush, method of tooth brushing, use of inter-dental aid, use of tobacco, use of alcohol and causes of bad breath were significantly associated with gender variable. Conclusions: Awareness with respect to oral health (using fluoridated toothpaste) among students was adequate. However, awareness of usage of toothbrushes and non-practicing tobacco and alcohol habit show the oral health knowledge in these students. The correct knowledge about maintaining good oral health needs to be given to the individuals in an effective manner at earliest so that it becomes a part of their life style.